1994
DOI: 10.1111/j.1365-2141.1994.tb06749.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial discrepancy between the one‐stage and two‐stage factor VIII methods in a subgroup of patients with haemophilia A

Abstract: A higher result for plasma factor VIII:C measured by the one-stage as compared with the two-stage method has been described in some patients with haemophilia A or with von Willebrand's disorder. We used both methods to measure FVIII:C in 95 patients with haemophilia A. The results were equivalent in all 21 patients with severe haemophilia (16 families) and in 45 of the patients with mild or moderate haemophilia (18 families). However, the results were discrepant (FVIII:C by one-stage assay 2-7-fold higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
111
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 8 publications
10
111
1
Order By: Relevance
“…Several groups have reported that a subgroup of mild haemophilia A patients have discrepancy between the activity of FVIII as determined using different types of assay [1][2][3]. More than 20% of mild haemophilia A patients are associated with assay discrepancy, where a twofold difference between results obtained with different assay systems is considered as discrepant [1].…”
Section: Steve Kitchenmentioning
confidence: 99%
“…Several groups have reported that a subgroup of mild haemophilia A patients have discrepancy between the activity of FVIII as determined using different types of assay [1][2][3]. More than 20% of mild haemophilia A patients are associated with assay discrepancy, where a twofold difference between results obtained with different assay systems is considered as discrepant [1].…”
Section: Steve Kitchenmentioning
confidence: 99%
“…One type of discrepancy is the lower twostage form, in which patients have reduced FVIII:C2 or FVIII:CR compared to FVIII:C1 activity and exhibit bleeding patterns consistent with the lower FVIII:C2 value. 2 The other type of discrepancy is the lower one-stage form in which the FVIII:C1 is reduced compared to that determined by the FVIII:C2 or FVIII:CR assay and in which little bleeding is reported. 4,5 We assessed FVIII:C assay discrepancy in 84 patients and female carriers from the Sheffield Haemophilia and Thrombosis Centre with FVIII:C levels between 5 and 50 IU/dL using a number of FVIII:C assays and also examined the value of rotational thromboelastometry (ROTEM) and calibrated automated thrombography (CAT) in the diagnosis of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 30% of patients show marked differences in FVIII:C activity when assayed by the three methods and are regarded as assay discrepant. [2][3][4] The differences in levels may be 2-fold or greater and for some patients, one or more of the FVIII:C assays may be in the normal range, potentially leading to an incorrect diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is easier to use and therefore used more commonly. Recently significant assay discrepancy has been recognised in the FVIII:C measurements in approximately one-third of mild haemophilia A patients (2)(3)(4).…”
mentioning
confidence: 99%